Development and Implementation of Some Advanced Web Server Protection Methods - Petrosyan, Arthur S.; Petrosyan, Gurgen S. (Mathematical Problems of Computer Science, 2021)
Article describes the development work done in the Academic Scientific Research Computer Network of Armenia (ASNET-AM) managed by the Institute for Informatics and Automation Problems (IIAP) of the National Academy of Sciences of the Republic of Armenia (NAS RA) regarding the implementation of web server protection and hardening. Some advanced methods and solutions implemented recently within ASNET-AM Web Hosting Services are being described. Based on the experience of ASNET-AM Web Hosting Services the best practice recommendations about secure web hosting environment implementation are given.